2016
DOI: 10.1136/jnnp-2015-312838
|View full text |Cite
|
Sign up to set email alerts
|

Randomised, waiting list controlled trial of cognitive–behavioural therapy for persistent postconcussional symptoms after predominantly mild–moderate traumatic brain injury

Abstract: BackgroundPersistent post-concussional symptoms (PCS) can be a source of distress and disability following traumatic brain (TBI). Such symptoms have been viewed as difficult to treat but may be amenable to psychological approaches such as cognitive behaviour therapy (CBT). ObjectivesTo evaluate the effectiveness of a 12-session individualised, formulation-based CBT program. MethodTwo-centre randomised waiting list controlled trial with 46 adults with persistent PCS after predominantly mild-to-moderate TBI (52%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
72
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 49 publications
3
72
0
1
Order By: Relevance
“…From the 7 studies meeting the inclusion criteria, there was a total of 1108 adult participants of which 68.8% (n = 763) were male. The participants ranged from 18 to 80 years of age and were mostly from the United States (n = 919), Denmark (n = 155), the Netherlands (n = 91), and England (n = 46) . Of the 7 studies, 3 studies focused on military staff and 4 focused on nonmilitary persons .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From the 7 studies meeting the inclusion criteria, there was a total of 1108 adult participants of which 68.8% (n = 763) were male. The participants ranged from 18 to 80 years of age and were mostly from the United States (n = 919), Denmark (n = 155), the Netherlands (n = 91), and England (n = 46) . Of the 7 studies, 3 studies focused on military staff and 4 focused on nonmilitary persons .…”
Section: Resultsmentioning
confidence: 99%
“…The participants ranged from 18 to 80 years of age and were mostly from the United States (n = 919), Denmark (n = 155), the Netherlands (n = 91), and England (n = 46) . Of the 7 studies, 3 studies focused on military staff and 4 focused on nonmilitary persons . Of the studies that focused on military staff, 2 studies enrolled active duty or active reserve/guard duty service members with confirmed or suspected mTBI and one study focused on veteran military staff.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations